2022
DOI: 10.3390/ma15207346
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Non-Destructive Evaluation of the Mechanical Characteristics of a Sustainable Concrete Incorporating Industrial Waste

Abstract: Structural materials sustainability is gaining popularity across the globe at present. Reusing natural resources, building, demolition debris, and solid waste are the most apparent tools to make construction more environmentally friendly. Traditional concrete is believed to be less durable, stronger, environmentally friendly, and socially and commercially feasible than industrial waste concrete. The evolution of non-destructive testing (NDT) across time has not been investigated in depth by researchers. An exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…There is a particular minimum strength value that each kind of concrete should meet. It is important that the concrete achieves the guaranteed strength without significantly exceeding it, as this could indicate an inadequate composition of the concrete mix [1,60]. According to the results in Table 7, variable proportions of concrete ingredients, including sand, gravel, cement, water, SSFA, and chemical admixtures, have a considerable impact on the strength of concrete mixes.…”
Section: Analysis Of Strength Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a particular minimum strength value that each kind of concrete should meet. It is important that the concrete achieves the guaranteed strength without significantly exceeding it, as this could indicate an inadequate composition of the concrete mix [1,60]. According to the results in Table 7, variable proportions of concrete ingredients, including sand, gravel, cement, water, SSFA, and chemical admixtures, have a considerable impact on the strength of concrete mixes.…”
Section: Analysis Of Strength Testsmentioning
confidence: 99%
“…Sand, gravel, and cement are just a few of the ingredients used to make concrete. In order to impart particular performance attributes, extra chemical admixtures are also used in the concrete mix [1]. The United States (72 million metric tons (MMT)), the Netherlands (54 MMT), Turkey (12 MMT), India (12 MMT), France (11 MMT), Italy (10 MMT), Bulgaria (8.4 MMT), Spain (5.7 MMT), and Poland (5.5 MMT) were the world's top producers of sand and gravel in 2021 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of mixed seawater and the hostile maritime environment make steel corrosion a severe issue, reducing the service life of coral concrete structures significantly [1][2][3][4][5][6][7][8][9]. Methods for protecting marine concrete reinforcement from corrosion, such as choosing corrosion-resistant materials, adding rust inhibitors for reinforcement, applying surface coatings, cathodic protection, and electrochemical dechlorination, are equally beneficial for coral concrete [10][11][12][13][14][15][16][17]. The protection of reinforcement in coral aggregate concrete (CAC) is currently being studied by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the maximum compressive strength could be achieved when using 10% rubber, 15% fly ash, and 15% silica fume. Umar et al [26] assessed the compressive strength of sustainable concrete containing coal bottom ash (CBA) and waste glass sludge (WGS). They reported that incorporating 10% CBA and WGS improved the porosity of concrete.…”
Section: Introductionmentioning
confidence: 99%